Fish debris abundance and fluxes in sediment core M77/2_024-5 - Renato Salvatteci (PANGAEA, 2022)
This dataset includes fish vertebrae abundances and fluxes obtained from core M77/2-024-5. Sediment core M77/2-024-5 (11°05.01 extquotesingleS; 78°00.91 extquotesingleW) was collected at 210 meters depth off Peru during Meteor expedition M77/2 in 2008 (Meteor station No. M772/677). Fish debris quantification and identification were determined in 60 samples along core M77/2-024-5 from 1093 to 1388 cm depth corresponding to 110.7 to 137.8 kyr BP. Sediment samples consisted of an average of 41 g of wet material, which yields 16.3 g of dry sediment. The fish vertebrae identification includes the following species/groups: anchovy (Engraulis ringens), goby-like fishes, juvenile fishes, Vinciguerria lucetia, hake (Merluccius gayi peruanus), blue lanternfish (Tarletonbeania crenularis), eel-shaped fish and other unidentified species. The fish debris were quantified and identified with the help of scale and vertebrae collections. The fish debris fluxes (#debris exttimes cm-2 exttimes y-1) were calculated by multiplying the fish debris abundance (number of fish debris x g-1) by the sedimentation rates (cm x y-1) by the dry bulk density (g x cm-3). Finally, the fluxes were multiplied by 1000.